SPONCER (Smart Pond Controller) Pengendali Lingkungan Air Kolam Guna Optimalisasi Produksi Ikan Sidat di Budi Fish Farm, Ngaglik, Sleman, Daerah Istimewa Yogyakarta - Sandy, Naufal Kurnia (Jurnal Edukasi Elektro, 2019)
Eel (Anguilla sp.) Is one of the best-selling fish in international markets such as Japan, Hong Kong, Germany, Italy and several other countries. For example, in Japan, which has as much as 600 tons of eel needs every month, while Indonesia is only able to meet eel needs of 500 tons per month. Eel is susceptible to water environment conditions such as temperature and pH. Eel has ideal conditions, namely 27 â„ƒ -29 â„ƒ and pH 6-9. Inappropriate conditions will trigger death. SPONCER is an intelligent eel fish technology investment equipped with temperature sensors, pH sensors, arduino, photovoltaic cells, and water filters that function to maintain optimal temperature and pH for eel fish life automatically. SPONCER can reduce eel mortality by 57.14% so that it can contribute to increasing eel productivity in the international market. Keywords: Anguilla  sp., Innovation, Automation